DEVELOPMENT OF A BIOCOMPOSITE MATERIAL WITH BIOLEATHER PROPERTIES BASED ON LOCAL FRUIT PEEL WASTE AND EVALUATION OF ITS PHYSICOTECHNOLOGICAL PROPERTIES - S.N.Obloberdiyev; G.Sh.Korabekova; F.Sh.G‘ulomova; M.J.Bekmurodova; Sh.E.Ulashova; Z.A.Madusmonova (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. This article studies the technology of obtaining a biocomposite material with bio-leather properties based on local fruit peel waste. In the study, samples were prepared using fruit peel powder, natural biopolymers and plasticizers, and their appearance, flexibility, density, water resistance and surface structure were evaluated. The results showed that fruit peel waste can be used to obtain an environmentally safe biocomposite material similar to bio-leather.